Isolation of Chemical Constituent from Justicia aurea - KUMAR SRIVASTAVA, SHARAD; BAHADUR, FATEH (Asian Journal of Chemistry, 2010)
β-Sitosterol has been isolated for the petroleum ether extract and choline from the ethanolic extracts of Justicia aurea. The structures were established by spectral analysis and m.p. determination.